1996
DOI: 10.1093/ageing/25.4.310
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained Macrocytosis in Elderly Patients

Abstract: One hundred and twenty-four patients over the age of 75 years were assessed for the cause of their macrocytosis (MCV > 95 fl). A definitive diagnosis was reached in 75/124 (60%) by non-invasive techniques. The remainder underwent a bone marrow biopsy yielding a definitive diagnosis in a further six patients who had an identifiable myelodysplastic syndrome (MDS). A high proportion of the remainder had morphological abnormalities which fitted with no recognized pathological entity. It is suggested that these may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 9 publications
3
25
0
1
Order By: Relevance
“…However, their study has excluded drug induced causes. Mahmoud et al [16] have studied 124 patients in the age group of C75 years and found a higher incidence of hematological diseases and malignancy associated with macrocytosis. Breedveld et al [17] and Seppa et al [5] have reported Vitamin deficiency and alcoholism as the most frequent etiological factors, which is similar to the findings in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, their study has excluded drug induced causes. Mahmoud et al [16] have studied 124 patients in the age group of C75 years and found a higher incidence of hematological diseases and malignancy associated with macrocytosis. Breedveld et al [17] and Seppa et al [5] have reported Vitamin deficiency and alcoholism as the most frequent etiological factors, which is similar to the findings in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Though not specific for one condition, an elevated MCV of [100 fl, is a useful parameter directing further investigations which can ultimately lead to a definitive diagnosis in 75% of cases [16]. It may be the only indicator of vitamin deficiency and alcoholism [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15]. In peripheral smear examinations, the presence of macro-ovalocytes with MCV more than 115 fL and hypersegmented neutrophils, along with anisocytosis and poikilocytosis affects a megaloblastic disorder associated with B12 or folate deficiency.…”
Section: Macrocytosis Can Be Identified By Two Methods-mentioning
confidence: 99%
“…); serum transferrin, B 12 and folic acid were measured by immunofluorescence on IMX (Abbott). Serum chemistry including creatinine, alkaline phosphatase, bilirubin, proteins, transaminase and lactate dehydrogenase were determined by Model 717 Automatic Analyzer (Hitachi).…”
Section: Hematological and Laboratory Determinationsmentioning
confidence: 99%